Pengembangan Sistem Informasi Manajemen Kelas (Studi pada: SDN Mulyorejo 3 Malang) - Dhevanda Savira Ibadillah; Satrio Agung Wicaksono; Welly Purnomo (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
School is an institution that has several components that must be managed such as curriculum and learning components. At SDN Mulyorejo 3 Malang, some of the tasks in these components, such as scheduling activities, are still done manually using a spreadsheet and require a long time to generate a schedule. In addition, class management activities are not good because all subjects are contained in one classroom and attendance activities are carried out through WhatsApp groups. Therefore, to solve this problem, the school wants to build a system that can support these activities. The system was developed using the waterfall method in which there are stages requirements analysis, system design, system implementation using the CodeIgniter framework, and system testing using black box testing and user acceptance testing. Based on the results of black box testing, it was found that the system developed was in accordance with the design made. While the results of user acceptance on TU staff get a value of 94.28% which means that the system can be received very well. Then the results of user acceptance on the teacher get a value of 50% which means that the system is quite acceptable. While the results of user acceptance on students get a value of 87.5% which means that the system can be received very well.